2020
DOI: 10.1130/abs/2020am-357462
|View full text |Cite
|
Sign up to set email alerts
|

EXTREME CAPILLARY HETEROGENEITIES AND IN SITU FLUID COMPARTMENTALIZATION DUE TO CLUSTERS OF DEFORMATION BANDS IN SANDSTONES

Abstract: Previous work has shown that individual deformation bands act like capillary barriers and influence fluid saturation. More common in nature, however, are clusters of deformation bands that form complex three dimensional geometries. The aim of this study is to analyze the extent and mechanisms of fluid compartmentalization due to clustered bands. Drainage multiphase fluid flow experiments were performed on a Navajo sandstone core sample characterized by diversely oriented clusters of deformation bands, that sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
(129 reference statements)
0
1
0
Order By: Relevance
“…Fossen and Bale (2007) evaluated the reduction in flow efficiency based on the differential form of steady-state Darcy equation and concluded that the permeability difference between the host rock and the deformation band should be higher than four orders of magnitude to have a significant effect on fluid flow. Romano et al (2020) and Romano et al (2021) showed via core-scale fluid flow simulations that deformation bands can act as strong capillary barriers and cause fluid compartmentalization in sandstones. Numerical simulations were also performed for carbonate (Rotevatn et al 2016) and siliciclastic (Matthai et al 1998;Sternlof et al 2006;Zuluaga et al 2016;Awdal et al 2020) reservoirs to examine the influence of deformation bands on total recovery with respect to their permeability contrast with the host rock.…”
Section: Introductionmentioning
confidence: 99%
“…Fossen and Bale (2007) evaluated the reduction in flow efficiency based on the differential form of steady-state Darcy equation and concluded that the permeability difference between the host rock and the deformation band should be higher than four orders of magnitude to have a significant effect on fluid flow. Romano et al (2020) and Romano et al (2021) showed via core-scale fluid flow simulations that deformation bands can act as strong capillary barriers and cause fluid compartmentalization in sandstones. Numerical simulations were also performed for carbonate (Rotevatn et al 2016) and siliciclastic (Matthai et al 1998;Sternlof et al 2006;Zuluaga et al 2016;Awdal et al 2020) reservoirs to examine the influence of deformation bands on total recovery with respect to their permeability contrast with the host rock.…”
Section: Introductionmentioning
confidence: 99%